1998
DOI: 10.1161/01.hyp.31.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase and Blood Pressure

Abstract: Abstract-In the present studies, the influence of inducible nitric oxide synthase (NOS) inhibition with aminoguanidine on renal function and blood pressure was examined in rats. Intravenous aminoguanidine infusion (60 mg ⅐ kg Ϫ1 ⅐ hr Ϫ1) for 40 minutes to anesthetized Sprague-Dawley rats (nϭ7) resulted in no significant changes in mean arterial pressure or renal cortical blood flow, while medullary blood flow was slightly increased. Despite minimal effects on renal blood flow, urine flow was significantly decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 37 publications
7
82
0
Order By: Relevance
“…Chronic intravenous infusions of aminoguanidine in Sprague-Dawley rats that resulted in a 49% reduction of Ca 2ϩ -independent NOS (inducible NOS) in the renal medulla, produced a salt-dependent form of hypertension with mean arterial pressure rising nearly 15 mmHg when these rats were fed a high-salt (4%) diet. The results also suggested that these events occurred independently of renal vascular changes, because intravenous infusion of this inhibitor at the same dose in anesthetized rats resulted in no significant changes in mean arterial pressure, CBF, or MBF, whereas urine flow and sodium excretion were significantly decreased (60).…”
Section: Influence Of Medullary No Production On Blood Pressure Salt mentioning
confidence: 82%
See 2 more Smart Citations
“…Chronic intravenous infusions of aminoguanidine in Sprague-Dawley rats that resulted in a 49% reduction of Ca 2ϩ -independent NOS (inducible NOS) in the renal medulla, produced a salt-dependent form of hypertension with mean arterial pressure rising nearly 15 mmHg when these rats were fed a high-salt (4%) diet. The results also suggested that these events occurred independently of renal vascular changes, because intravenous infusion of this inhibitor at the same dose in anesthetized rats resulted in no significant changes in mean arterial pressure, CBF, or MBF, whereas urine flow and sodium excretion were significantly decreased (60).…”
Section: Influence Of Medullary No Production On Blood Pressure Salt mentioning
confidence: 82%
“…Tan et al (120) observed hypertensive responses in the absence of any measurable changes in renal plasma flow or GFR with chronic intravenous administration of aminoguanidine in salt-resistant Dahl R rats exposed to a high-salt diet, consistent with predominant tubular effects. Recent work by Kakoki et al (42) and Mattson et al (60) using a variety of NOS isoform-specific inhibitors indicated that NO derived from NOS I and/or NOS II has minimal effect on blood flow in the renal medulla (42,60). The results also suggest that the enhanced salt sensitivity with NOS inhibition may be largely a consequence of a reduction of NOS I and NOS II activity within the deep nephrons of the renal medulla.…”
Section: Influence Of Medullary No Production On Blood Pressure Salt mentioning
confidence: 94%
See 1 more Smart Citation
“…Inhibition of NOS in the renal medulla has isoform-specific effects. NOS1 inhibition reduces NO levels in the medulla and induces salt-sensitive hypertension but fails to alter medullary perfusion (50,74,77). Global inhibition of NOS1, NOS2, and NOS3 isoforms with nonselective blockers decreases medullary NO levels and induces salt retention and hypertension.…”
Section: Medullary Po2 and Perfusion Of The Medullamentioning
confidence: 99%
“…The NOS inhibitor aminoguanidine (AG) was used to confirm whether NOS inhibition prevents both the early aneurysmal changes and the formation of aneurysms in rats. 6 We also examined the mechanism of iNOS induction in the development of aneurysms. Clinical and epidemiological evidence suggests that the heightened hemodynamic stress due to an increase in blood flow may be an important factor underlying aneurysm development.…”
mentioning
confidence: 99%